Integrating Science Contexts into a PBL-ViMomath Model: A Needs Analysis for Enhancing Elementary Pre-Service Teachers’ Mathematical Problem-Solving in Geometry and Measurement - Maifit Hendriani; I. Made Arnawa; Melva Zainil (Postgraduate, University of Mataram, 2025)
This study aims to analyze the needs for developing an integrated instructional model to enhance elementary pre-service teachers’ mathematical problem-solving skills in geometry and measurement. A qualitative needs analysis was conducted through diagnostic tests, interviews, classroom observations, and document analysis involving pre-service teachers and educators. Findings reveal significant difficulties in understanding abstract concepts, low confidence in problem-solving, and minimal integration of science contexts in current mathematics instruction. Despite these challenges, participants expressed strong interest in interdisciplinary, context-based learning. The results highlight the potential of integrating video and mathematical modeling into Problem-Based Learning (PBL) to improve problem comprehension and engagement. Based on the data, the PBL-ViMo model—combining PBL, video-based problem orientation (Vi), and mathematical modeling (Mo)—was developed as a responsive and structured approach. Video facilitates visual understanding of real-world problems, while modeling provides a systematic framework for translating contexts into mathematical solutions. The study concludes that the PBL-ViMo model addresses identified learning gaps and offers an innovative, learner-centered strategy to strengthen both conceptual understanding and pedagogical competence in mathematics teacher education.